Analisis Kesalahan Perhitungan PPh Pasal 21 Karyawan Tidak Tetap Penerima Upah Harian pada PT SS - Adisti, Elsa Aulia; Sucahyati, Diarany (Masyarakat Ekonomi Syariah Bogor, 2025)
Accuracy in calculating Income Tax Article 21 is essential for employers as tax withholders, especially for non-permanent employees receiving daily wages who have special tax treatment. This study aims to analyze and identify errors in the calculation of Income Tax Article 21 made by PT SS and analyze the causes of these errors. The research method used is a case study with a descriptive approach, through interviews and documentation of payroll data. The results showed that errors occurred in two main aspects, specifically the application of inappropriate withholding rates and improper treatment of income deduction components. The errors were caused by the company's lack of understanding of tax provisions and mistakes in the formulation of the payroll system. As a result, there were three employees who experienced calculation errors that led to excess tax withholding. This study emphasizes the importance of a good understanding of tax regulations and also highlights the importance of the role of tax consultants in helping companies ensure the accuracy of tax calculations.